2017
DOI: 10.1177/1932296817699638
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Variability of Insulin When Administered by Jet Injection

Abstract: Background:Jet injection has been shown to accelerate the absorption and action of rapid-acting insulin. In this study, we compared the variability of absorption characteristics between jet injection and conventional administration of the rapid-acting insulin analogue aspart.Methods:A total of 30 healthy volunteers were enrolled in this randomized controlled blinded parallel study. On two test days, they received insulin aspart (0.2 units/kg body weight), either by jet injection or conventional pen, followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Use of jet injection, where insulin is administered at high velocity across the skin, instead of conventional pen administration has been shown to accelerate absorption of insulin aspart in healthy subjects and persons with diabetes [ 162 , 163 ]. The jet injection results in the depot being dispersed in a spray-like manner in the SC tissue, thus increasing the surface-to-volume ratio of the injection depot that is likely the mechanism behind the accelerated absorption [ 163 ].…”
Section: Physiological Factors and Factors Related To The Injectiomentioning
confidence: 99%
See 1 more Smart Citation
“…Use of jet injection, where insulin is administered at high velocity across the skin, instead of conventional pen administration has been shown to accelerate absorption of insulin aspart in healthy subjects and persons with diabetes [ 162 , 163 ]. The jet injection results in the depot being dispersed in a spray-like manner in the SC tissue, thus increasing the surface-to-volume ratio of the injection depot that is likely the mechanism behind the accelerated absorption [ 163 ].…”
Section: Physiological Factors and Factors Related To The Injectiomentioning
confidence: 99%
“…The jet injection results in the depot being dispersed in a spray-like manner in the SC tissue, thus increasing the surface-to-volume ratio of the injection depot that is likely the mechanism behind the accelerated absorption [ 163 ]. Elsemiek et al observed a 40% shorter T max and a significantly higher C max with jet compared to pen administration in healthy subjects [ 162 ]. Moreover, use of jet injection has also been reported to be beneficial in terms of diminishing the obesity-associated delay in insulin absorption compared to pen injections [ 129 , 164 ].…”
Section: Physiological Factors and Factors Related To The Injectiomentioning
confidence: 99%
“…A run-in period from week 1 to the end of week 4 was implemented to allow treatment adjustment. Since regular insulin (RI) injected through a needle-free injector has shown a similar pharmacological profile to rapid-acting insulin [9,10], we reduced the insulin dosage when switching the insulin injecting device from a CIP to the NFII to avoid transient hyperinsulinemia, as this may lead to hypoglycemia. In patients previously using premixed insulin, those assigned to the NFII group had their insulin dosage reduced by 10%.…”
Section: Interventionsmentioning
confidence: 99%
“…Needle-free injections of insulin have considerably enhanced insulin absorption and the consequent glucose-lowering effect, as well as achieving faster correction of hyperglycemia in short-term and small-scale trials in healthy volunteers and patients with diabetes [9,10]. However, whether these benefits can translate to better or equivalent glycemic control compared with needle-based insulin injections and improve patient satisfaction with treatment needs to be tested in larger and longer-term trials, since insulin treatment is a long-term therapy administered by patients themselves in ambulatory settings under the supervision of clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of these devices are that the needle is hidden from view and the needle is inserted through the skin rapidly. Automatic injection devices for specific insulin injectors are available …”
Section: Administration Of Insulinmentioning
confidence: 99%